Influence of Talent Management Practices on Performance of State Corporations in Kenya - Wanjugu, Nderi Caroline; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
The greatest asset for any Country in general and Organization in particular is its human capital. In the recent past the performance of State Corporations is becoming a challenge in public service resulting to loss of government funds, this is great loss in a country. Talent management is therefore crucial and indispensable for any organization’s management practice. Talent Management Practices has been recognized by many authors as an important Human resource management practice. Talent management practices are important in the ever changing global environment and in the in state corporations, are no exception. The objective of this study was to determine the influence of talent management practices on State Corporations’ performance in Kenya. The specific objectives were; to evaluate the influence of performance Management on firm performance, to establish the influence of training and development on firm performance, to establish the influence of reward systems on firm performance and to assess the influence of employee empowerment on firm performance of State Corporations in Kenya. The scope of the study was the State Corporations in Kenya. The target population of the study was the Human Resources managers/equivalent in all the 147 state Corporations in Kenya. The study used census approach to reach all the Human Resources managers/equivalent in all the 147 state Corporations in Kenya. A questionnaire was used as the main data collection tool to collect primary data. Secondary data on state corporations’ performance were obtained from documentaries and published reports available. Piloting of the instruments was done before the actual data collection to test on the reliability. Authorization letter for data collection was obtained from Jomo Kenyatta University. The primary data collected was analysed through the use of descriptive statistics where the SPSS Ver. 21.0 was used as the aid tool. Frequency tables, percentages, mean and standard deviation, pie charts, charts and graphs were used to present the analysed data. The study found out that reward management leads to improved performance in the state corporations in Kenya by enhancing target achievement, improving customer satisfaction and improving corporation ranking, training and development leads to improved performance in the state corporations in Kenya by enhancing target achievement, improving customer satisfaction, and improving corporation ranking,; performance management in the state corporations in Kenya leads to improved performance by enhancing target achievement, improving customer satisfaction, and improving corporation ranking, employee empowerment in state corporations in Kenya leads to improved performance by enhancing target achievement, improving customer satisfaction and improving corporation ranking. The study concluded that talent management practices in state corporations in Kenya improve performance. the study recommended that state corporations introduce a more competent strategy for rewarding their employees, training and development should be a practice employed on all employees of the state corporations not just those on top, and employee empowerment should not only be done to the top and middle level employees but to those at the bottom level management as well for they often feel left out